Inhalation of Nitrous Oxide Expands Epidural Air Bubbles. Issue 2 (March 1996) - Petty, Robert; Stevens, Rom; Erickson, Scott; Lucio, John; Kao, Tzu-Cheg
Abstract : Background and Objectives: Epidural air bubbles are known to persist for more than 24 hours after injection. Nitrous oxide may cause expansion of these bubbles. Methods: Nine dogs were anesthetized. Ten mL air and 9 mL of iophendylate were injected into the lumbar epidural space. Control animals (n = 3) breathed halothane in 100% oxygen. Experimental animals (n = 6) breathed halothane in 70/30 nitrous oxide/oxygen. Lateral radiographs were taken before and just after injection, and again 3 hours after breathing either 70% nitrous oxide or 100% oxygen. Epidural space pressure was monitored and recorded during these 3 hours. Results: In all experimental animals, an increase in bubble size was observed. In the control animals, bubble size either remained the same or decreased. Epidural space pressure did not change in any animal. Conclusions: Inhalation of nitrous oxide results in expansion of epidural air bubbles. This may cause displacement of epidural local anesthetics if large volumes of air are present in the epidural space.